2014
DOI: 10.14486/ijscs84
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTIVE CONTRIBUTION OF MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES ON THE RESULT OF RUNNING THE 60m HURDLES IN BOYS AGED 12-13 YEARS

Abstract: The subject of this study is to determine predictive contributions of morphological characteristics and motor abilities on the 60m hurdles, with an aim to form a group of easily applicable field tests so as to identify boys who are talented in hurdle racing. The subject sample of this study was comprised of 60 boys aged 12-13. The variable sample consisted of a 60m hurdles criterion variable and a set of 13 predictor variables comprising of morphological characteristics, speed-strength abilities and the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As studies of other authors (Bujak et al, 2014;Iskra & Mynarski, 2000) show, the body build is not the most important factor determining the time of hurdle sprint race in groups of untrained youth. Otsuka (2013) Accordingly, hurdles can be seen as an attractive form of a comprehensive assessment of physical fitness of untrained girls.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As studies of other authors (Bujak et al, 2014;Iskra & Mynarski, 2000) show, the body build is not the most important factor determining the time of hurdle sprint race in groups of untrained youth. Otsuka (2013) Accordingly, hurdles can be seen as an attractive form of a comprehensive assessment of physical fitness of untrained girls.…”
Section: Discussionmentioning
confidence: 85%
“…The results of fitness analysis (including speed, endurance, strength and mobility in the joints) in the context of hurdle training were analyzed by many authors (Alricsson et al, 2001;Bujak, Smajlovic, Likic & Omerowic, 2014;Ikeda & Aogagi;Iskra & Mynarski, 2000;Iskra et al, 2006;Otsuka, Ito M. & Ito A., 2010). The research carried out in the group of Polish girls showed that the "training" using hurdles can be an effective means to improve the running speed.…”
Section: Discussionmentioning
confidence: 99%
“…The research offers to continue studies focusing on bursts of strength in this age group, taking into account the individual's sporting experience and physiological development; it is also important that the program's training includes other components (strength and speed, nutritional advice, and/or mental health) that can contribute to power bursts (Pena-Brito et al, 2023). According to (Bujak et al, 2014) states that the hurdle drill is one of the most demanding exercises in terms of motor and technical skills characterized by fast and powerful movements. The application of the hurdles technique is hurdles with a step pattern.…”
Section: Introductionmentioning
confidence: 99%